Chemokine and Free Fatty Acid Levels in Insulin-Resistant State of Successful Pregnancy: A Preliminary Observation - Katsuhiko Naruse; Taketoshi Noguchi; Toshiyuki Sado; Taihei Tsunemi; Hiroshi Shigetomi; Seiji Kanayama; Juria Akasaka; Natsuki Koike; Hidekazu Oi; Hiroshi Kobayashi (Mediators of Inflammation)
Increased insulin resistance and inflammatory action are observed in pregnancy-induced hypertension (PIH), but similar insulin resistance is observed also in successful pregnancy. To estimate insulin resistance and inflammatory activity in normal pregnancy and PIH, serum concentrations of free fatty acids (FFA; corrected with albumin to estimate unbound FFA), monocyte chemoattractant protein (MCP)-1, and high-molecular weight (HMW) adiponectin were measured in severe PIH patients with a BMI less than 25 kg/m2 and were measured 3 times during the course of pregnancy in women with normal pregnancies. FFA/albumin, MCP-1, and HMW adiponectin concentrations were significantly higher in PIH patients than in women with normal pregnancies. The 3 measurements of FFA/albumin showed a significant increase through the course of uncomplicated pregnancies. In contrast, MCP-1 and HMW adiponectin were significantly decreased during the course of pregnancy. These results suggest that the reduced MCP-1 concentration in normal pregnancy may be a pathway to inhibit the induction of pathological features from physiological insulin resistance and homeostatic inflammation.